Alkali-activated cementing material formula design method for rapid repair of concrete pavement

Through extreme apex design method and X-ray fluorescence spectroscopy analysis, the optimal composition ratio of the excitant and aluminosilicate minerals in alkali-excited gelling materials was determined, which solved the problem of poor adaptability of the material formula and achieved efficient and accurate results of rapid repair of concrete pavement.

CN119851826APending Publication Date: 2025-04-18STATE GRID HEBEI ELECTRIC POWER CO LTD CONSTR CO +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411926269.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

In terms of rapid repair of concrete pavement, alkali-excited gelling materials have a wide variety of solid waste raw materials and different properties, and the adaptability of different raw materials and alkali-excited agents is poor, resulting in poor formulation adaptability, which limits its application.

Method used

The extreme apex design method was used, combined with X-ray fluorescence spectroscopy analysis, and the optimal composition ratio of the exciter and high-potentially active aluminosilicate mineral was determined. The optimal ratio of the gelled material was calculated through DOE mixture design and response variable optimization.

Benefits of technology

The rapid and accurate calculation of cemented materials using alkali to stimulate cemented materials for rapid repair of concrete pavements has been achieved, which improves the adaptability of materials and the quality of repairing pavements, and reduces the exploration steps in the traditional design process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119851826A_ABST
    Figure CN119851826A_ABST
Patent Text Reader

Abstract

The invention provides a formula design method of an alkali-activated cementing material for rapid repair of a concrete pavement, and belongs to the technical field of repair materials for concrete pavements, the method comprises the following steps: determining the composition of an activator and a high potential activity aluminosilicate mineral in the cementing material and the mixing amount range of each component; according to the requirement of the target strength, an extreme vertex design method is adopted, and the optimal composition proportion of the excitant and the aluminosilicate mineral in the cementing material is determined. According to the method, a special calculation formula for the use amount of the exciting agent and an aluminosilicate limit value based on the fluidity ratio of aluminosilicate minerals and 7d activity are given, and an extreme vertex design method is matched, so that rapid and accurate calculation of the ratio of the alkali-activated cementing material for rapid repair of the concrete pavement is realized, and the problem that in the traditional mix proportion design process, the cost is low is solved. A process of gradually exploring a proper ratio according to different raw materials is needed, so that the adaptability of the alkali-activated cementing material and the quality of a repaired pavement are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of repair materials for concrete pavements, and in particular relates to a method for designing a formula of an alkali-activated cementitious material for rapid repair of concrete pavements. Background Art

[0002] Alkali-activated cementitious materials are hydraulic cementitious materials prepared by using alkali activators to activate the potential activity of aluminum silicate minerals. They are considered to be an alternative cementitious material for cement because of their low energy consumption, high strength, and good durability. Commonly used alkali activators include strong alkali (NaOH) and water glass (Na2O·nSiO2). Common potentially active silicate mineral raw materials are mostly industrial solid wastes, such as blast furnace slag, fly ash, steel slag, silica fume, metakaolin, slag, etc., which not only help solve the carbon emission problem of the cement industry, but also effectively achieve the role of solid waste disposal.

[0003] At present, alkali-activated cementitious materials have the following shortcomings in the rapid repair of concrete pavements: the solid waste raw materials in alkali-activated cementitious materials are of various types and have different properties. The adaptability of different solid waste raw materials to alkali activators varies greatly. The formula of alkali-activated cementitious materials developed with any raw material composition has poor adaptability, which limits its application in the field of rapid repair. Summary of the invention

[0004] The embodiment of the present invention provides a method for designing a formula of alkali-activated cementitious materials for rapid repair of concrete pavements, aiming to solve the problem that solid waste raw materials in alkali-activated cementitious materials are of various types and have different properties, and the adaptability of different solid waste raw materials to alkali activators varies greatly, resulting in poor adaptability of the same formula of alkali-activated cementitious materials.

[0005] To achieve the above object, the technical solution adopted by the present invention is: to provide a method for designing a formula of an alkali-activated cementitious material for rapid repair of a concrete pavement, the method comprising the following steps:

[0006] Determine the composition of the activator and high potential active aluminosilicate minerals in the cementitious material and the dosage range of each component;

[0007] According to the target strength requirement, the extreme vertex design method is adopted to determine the optimal composition ratio of the activator and aluminosilicate minerals in the cementitious material.

[0008] In one achievable manner, the composition of the activator includes sodium hydroxide particles, solid sodium silicate or liquid sodium silicate, and the dosage range of each component of the activator to the total cementitious material is calculated by formula (1):

[0009]

[0010] In the formula, ω1 is the amount of solid sodium silicate in the total cementitious material, ω2 is the amount of sodium hydroxide particles in the total cementitious material, s1 ——The content of SiO2 in solid sodium silicate, ω n1 ——Na2O content in solid sodium silicate, ω n2 ——The content of Na2O in sodium hydroxide particles; where ω s1 ,ω n1 ,ω n2 Derived from X-ray fluorescence spectroscopy.

[0011] In a feasible manner, the high potential active aluminosilicate mineral is selected from one or two of mineral powder, metakaolin, silica fume, and cement clinker, and needs to satisfy a 28d activity index of ≥85%.

[0012] In one feasible manner, the lower limit of the dosage of the high potential active aluminosilicate mineral in the total cementitious material is selected according to the 7d activity index of the raw material: when the 7d activity index is ≥115%, the lower limit is 0.0; when the 7d activity index is ≥105%, the lower limit is 0.1; when the 7d activity index is ≥95%, the lower limit is 0.2; when the 7d activity index is ≥75%, the lower limit is 0.3.

[0013] In one feasible manner, the amount of the high potential active aluminosilicate mineral in the total cementitious material is selected based on the fluidity ratio of the raw materials: when the fluidity ratio is ≥95%, the upper limit is 0.8; when the fluidity ratio is ≥85%, the upper limit is 0.7; when the fluidity ratio is ≥75%, the upper limit is 0.6; when the fluidity ratio is <75%, the upper limit is 0.5.

[0014] In an achievable manner, according to the target strength requirement, the extreme vertex design method is used to determine the optimal composition ratio of the activator and the high potential active aluminum silicate mineral in the cementitious material, including:

[0015] Step 1: Create a mixture design based on the composition of the activator and the high potential active aluminum silicate mineral in the cementitious material and the dosage range of each component to obtain an experimental design table;

[0016] Step 2: According to the proportion of each group of cementitious materials in the experimental design table, multiple groups of mortar test block models are prepared with the ratio of cementitious material: fine aggregate: water = 1:2.2:0.56. After molding, they are cured to 1d and 7d ages, and the compressive strength of the mortar test block models with different proportions at 1d and 7d ages is measured to obtain the mixture design experiment result table;

[0017] Step three: According to the compressive strength of the mortar test block models with different proportions at 1d and 7d, the mixed contour maps of the 1d and 7d compressive strengths are obtained respectively, and the response variable optimizer is used to optimize the 1d and 7d compressive strengths to obtain the optimal proportion of the target strength.

[0018] In one feasible method, in step one, based on the composition of the activator and high potential active aluminosilicate minerals in the cementitious material and the dosage range of each component, DOE mixture design is performed and the extreme vertex method is used to set the boundaries and linear constraints of each component in the cementitious material to obtain an experimental design table.

[0019] In one achievable manner, in step 2, in the proportion of each group of gelling materials, the amount of water used needs to be subtracted from the water content of the sodium hydroxide particles, solid sodium silicate or liquid sodium silicate.

[0020] In one achievable manner, in step 2, the prepared mortar test block model is a cuboid of 40 mm×40 mm×160 mm, or a cube of 70.7 mm×70.7 mm×70.7 mm.

[0021] In one feasible method, in step three, by analyzing the DOE mixture design, mixture regression is selected under the model fitting method, the minimum effect value in the mixture design experimental result table is deleted, and the regression equation is fitted to obtain the estimated regression coefficients of the 1d and 7d compressive strength; then the response tracker is used to verify the regression model, and the predicted values ​​of the compressive strength at the ages of 1d and 7d are read through the mixed contour map, and the compressive strength of the mortar specimen model at the ages of 1d and 7d is measured. If the difference between the test value and the predicted value of the compressive strength of the mortar specimen model at the ages of 1d and 7d is between -5% and 5%, it is determined that the mortar specimen model is relatively accurate and can be used for target strength prediction.

[0022] The method for designing a formula of alkali-activated cementitious materials for rapid repair of concrete pavements provided by the present invention has the beneficial effects compared with the prior art in that a special calculation formula for the amount of activator and an aluminosilicate limit based on the fluidity ratio of aluminosilicate minerals and the 7d activity are provided, and combined with an extreme vertex design method, rapid and accurate calculation of the proportion of alkali-activated cementitious materials for rapid repair of concrete pavements is achieved, eliminating the need for gradually exploring the appropriate proportion according to different raw materials in the traditional mix design process, thereby improving the adaptability of the alkali-activated cementitious materials and the quality of the repaired pavement. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 A Cox response tracking diagram of the 1d strength of the mortar test block model provided in an embodiment of the present invention;

[0024] Figure 2The Cox response tracking diagram of the 7d strength of the mortar test block model provided in the embodiment of the present invention;

[0025] Figure 3 A mixed contour map and an overlapping contour map of the 1d strength of the mortar test block model provided in an embodiment of the present invention;

[0026] Figure 4 A mixed contour map and an overlapping contour map of the 7d strength of the mortar test block model provided in an embodiment of the present invention;

[0027] Figure 5 Optimize plots for response variables;

[0028] Description of reference numerals: DETAILED DESCRIPTION

[0029] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0030] The formula design method of the alkali-activated cementitious material for rapid repair of concrete pavement provided by the present invention is now described.

[0031] The target strength of the repair material to be produced is set as follows: 1d compressive strength ≥35Mpa, 7d compressive strength ≥50MPa.

[0032] The method comprises the following steps:

[0033] First, the composition of the activator and the high potential active aluminum silicate mineral in the cementitious material and the dosage range of each component are determined, including the following steps:

[0034] (I) Determine that the activator includes solid sodium silicate (ω s1 =53.43%,ω n1 =26.91%), sodium hydroxide granules (analytical grade, ω n2 =77.50%); from formula (1), we can obtain ω1∈(0.045, 0.362), ω2∈(0.002, 0.098), and satisfy 26.91%ω1+77.50%ω2∈(0.05, 0.10).

[0035] (II) High potential active aluminosilicate minerals include mineral powder (7d activity index 98%, fluidity ratio 96%) and kaolin (7d activity index 118%, fluidity ratio <75%). The dosage range of mineral powder is 0.2-0.8, and the dosage range of kaolin is 0.0-0.5.

[0036] According to the target strength requirements, the extreme vertex design method is used to determine the optimal composition ratio of the activator and the high potential active aluminum silicate mineral in the cementitious material, including the following steps:

[0037] (III) According to the composition of the activator and high potential active aluminosilicate minerals in the cementitious material and the dosage range of each component, Minitab software was used to select four mixture components (including solid sodium silicate, sodium hydroxide particles, mineral powder and kaolin) through DOE mixture design and extreme vertex method, and the boundaries of the mixture components (see Table 1) and linear constraints (see Table 2) were set to obtain the mixture design experimental scheme design table (see Table 3).

[0038] Table 1 Boundaries of mixture components

[0039]

[0040] Table 2 Linear constraints on mixture components

[0041] constraint Lower limit Mineral powder Metakaolin Sodium silicate Sodium hydroxide Upper limit 1 0.05 0 0 0.2691 0.7750 0.10

[0042] Table 3 Mixture design experimental scheme design table

[0043]

[0044]

[0045]

[0046] (IV) According to the proportion of each group of cementitious materials in the experimental design table, 40mm×40mm×160mm rectangular or 70.7mm cubic mortar test block models (3 blocks in each group) were prepared with the ratio of cementitious material: fine aggregate: water = 1:2.2:0.56. The actual water content was deducted from the water content of sodium hydroxide particles and solid sodium silicate. After molding, the mortar blocks were cured to 1d and 7d ages. The compressive strength of mortar test blocks with different proportions at 1d and 7d ages was measured. The mixture design experiment results are shown in Table 4.

[0047] Table 4 Mixture design experiment results

[0048]

[0049]

[0050]

[0051] (V) Using Minitab software, by analyzing the DOE mixture design, selecting mixture regression under the model fitting method, deleting the minimum effect value in the mixture design experimental result table, fitting the regression equation, and obtaining the following results (Table 5, Table 6). The P value in the table is the significance level. If the significance level value is greater than 0.1, it is unqualified.

[0052] Table 5 Estimated regression coefficients of 1d intensity (component ratios)

[0053]

[0054] Table 6 Estimated regression coefficients of 7d intensity (component ratios)

[0055]

[0056] (VI) Validation of regression model. Figure 1 and Figure 2 ), the effects of individual factors can be shown by mixing contour plots (such as Figure 3 and Figure 4 Observe the changing trend in the whole range. Figure 3 and Figure 4 ) to read the predicted values ​​of compressive strength at 1d and 7d; prepare mortar test blocks according to the mix ratio in step (iv), and measure the compressive strength of the mortar test blocks at 1d and 7d. The predicted values ​​and test values ​​of each mix ratio are shown in Table 7 below.

[0057] Table 7 Predicted and tested compressive strength values ​​of mortar block models with different mix ratios

[0058] serial number O P Q R 1d compressive strength prediction value (MPa) 11 17 35 5 1d compressive strength test value (MPa) 11.3 17.4 34.2 4.9 The difference between the test value and the predicted value (%) 2.7 2.4 -2.3 -2.0 7d compressive strength prediction value (MPa) 40 46 58 20 7d compressive strength test value (MPa) 41.2 44.7 57.3 20.8 The difference between the test value and the predicted value (%) 3.0 -2.8 -1.2 4.0

[0059] The difference between the test value and the predicted value of the 1d and 7d compressive strength of the mortar specimen model is between -5% and 5%. The model is relatively accurate and can be used to predict the target strength.

[0060] (VII) Using the response variable optimizer (such as Figure 5 As shown in the figure, the optimal composition ratio of activator and aluminosilicate minerals in the cementitious material that meets the target strength (1d strength ≥ 30Mpa, 7d strength ≥ 50MPa) can be accurately calculated as mineral powder (68.00%), kaolin (1.93%), sodium silicate (27.01%), and sodium hydroxide (3.06%).

[0061] (VIII) After verification tests, the 1d strength was 35.4 MPa and the 7d strength was 58.2 MPa, which met the target strength requirements, indicating that the method of the present invention has high accuracy and can meet practical applications.

[0062] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described or recorded in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.

[0063] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for designing a formula of an alkali-activated cementitious material for rapid repair of a concrete pavement, characterized in that: The method comprises the following steps: Determine the composition of the activator and high potential active aluminosilicate minerals in the cementitious material and the dosage range of each component; According to the target strength requirement, the extreme vertex design method is adopted to determine the optimal composition ratio of the activator and aluminosilicate minerals in the cementitious material.

2. The method for designing a formula of an alkali-activated cementitious material for rapid repair of a concrete pavement according to claim 1, characterized in that: The activator comprises sodium hydroxide particles, solid sodium silicate or liquid sodium silicate. The dosage range of each component of the activator in the total cementitious material is calculated by formula (1): In the formula, ω1 is the amount of solid sodium silicate in the total cementitious material, ω2 is the amount of sodium hydroxide particles in the total cementitious material, s1 ——The content of SiO2 in solid sodium silicate, ω n1 ——Na2O content in solid sodium silicate, ω n2 ——The content of Na2O in sodium hydroxide particles; where ω s1 ,ω n1 ,ω n2 Derived from X-ray fluorescence spectroscopy.

3. The method for designing a formula of an alkali-activated cementitious material for rapid repair of a concrete pavement according to claim 2, characterized in that: The high potential active aluminosilicate minerals are selected from one or two of mineral powder, metakaolin, silica fume, and cement clinker, and must satisfy a 28d activity index of ≥85%.

4. The method for designing a formula of an alkali-activated cementitious material for rapid repair of a concrete pavement according to claim 3, characterized in that: The lower limit of the dosage of the high potential active aluminum silicate mineral in the total cementitious material is selected according to the 7d activity index of the raw material: when the 7d activity index is ≥115%, the lower limit is 0.0; when the 7d activity index is ≥105%, the lower limit is 0.1; when the 7d activity index is ≥95%, the lower limit is 0.2; when the 7d activity index is ≥75%, the lower limit is 0.

3.

5. The method for designing a formula of an alkali-activated cementitious material for rapid repair of a concrete pavement according to claim 4, characterized in that: The amount of the high potential active aluminosilicate mineral in the total cementitious material is selected according to the fluidity ratio of the raw materials: when the fluidity ratio is ≥95%, the upper limit is 0.8; when the fluidity ratio is ≥85%, the upper limit is 0.7; When the fluidity ratio is ≥75%, the upper limit is 0.6; When the fluidity ratio is less than 75%, the upper limit is 0.

5.

6. The method for formula design of alkali-activated cementitious material for rapid repair of concrete pavement according to any one of claims 1 to 5, characterized in that: According to the target strength requirement, the extreme vertex design method is used to determine the optimal composition ratio of the activator and the high potential active aluminum silicate mineral in the cementitious material, including: Step 1: Create a mixture design based on the composition of the activator and the high potential active aluminum silicate mineral in the cementitious material and the dosage range of each component to obtain an experimental design table; Step 2: According to the proportion of each group of cementitious materials in the experimental design table, multiple groups of mortar test block models are prepared with the ratio of cementitious material: fine aggregate: water = 1:2.2:0.

56. After molding, they are cured to 1d and 7d ages, and the compressive strength of the mortar test block models with different proportions at 1d and 7d ages is measured to obtain the mixture design experiment result table; Step three: According to the compressive strength of the mortar test block models with different proportions at 1d and 7d, the mixed contour maps of the 1d and 7d compressive strengths are obtained respectively, and the response variable optimizer is used to optimize the 1d and 7d compressive strengths to obtain the optimal proportion of the target strength.

7. The method for designing a formula of an alkali-activated cementitious material for rapid repair of a concrete pavement according to claim 6, characterized in that: In step 1, according to the composition of the activator and high potential active aluminosilicate minerals in the cementitious material and the dosage range of each component, the boundary and linear constraints of each component in the cementitious material are set through DOE mixture design and the extreme vertex method to obtain the experimental design table.

8. The method for designing a formula of an alkali-activated cementitious material for rapid repair of a concrete pavement according to claim 6, characterized in that: In step 2, in the proportion of each group of gelling materials, the amount of water used needs to be subtracted from the water content of the sodium hydroxide particles, solid sodium silicate or liquid sodium silicate.

9. The method for designing a formula of an alkali-activated cementitious material for rapid repair of a concrete pavement according to claim 6, characterized in that: In step 2, the prepared mortar test block model is a cuboid of 40 mm×40 mm×160 mm, or a cube of 70.7 mm×70.7 mm×70.7 mm.

10. The method for designing a formula of an alkali-activated cementitious material for rapid repair of a concrete pavement according to claim 6, characterized in that: In step three, by analyzing the DOE mixture design, mixture regression is selected under the model fitting method, the minimum effect value in the mixture design experimental result table is deleted, the regression equation is fitted, and the estimated regression coefficients of the 1d and 7d compressive strength are obtained; then the response tracker is used to verify the regression model, and the predicted values ​​of the compressive strength at the ages of 1d and 7d are read through the mixed contour map, and the compressive strength of the mortar specimen model at the ages of 1d and 7d is measured. If the difference between the test value and the predicted value of the compressive strength of the mortar specimen model at the ages of 1d and 7d is between -5% and 5%, it is determined that the mortar specimen model is relatively accurate and can be used for target strength prediction.